14.1% efficiency hybrid planar-Si/organic heterojunction solar cells with SnO2 insertion layer. (1st November 2018) - Chen, Lei; Gao, Zhongliang; Zheng, Yupeng; Cui, Mengqi; Yan, Hejin; Wei, Dong; Dou, Shangyi; Ji, Jun; Jia, Endong; Sang, Na; Liu, Kunhao; Ding, Xunlei; et al.
Highlight: The SnO2 insertion layer was introduced into the hybrid Si/organic solar cells. The band structure of Schottky barrier was replaced to reduce the barrier height. DFT simulations show the Si-O-Sn bonds electrostatic potential distribution. Electrostatic potential proves that electrons are easily transmitted from Si to Sn. Abstract: Hybrid planar-Si/organic heterojunction solar cells have gained considerable interest in the fabrication of cost-effective and high-efficiency devices. However, most of high power conversion efficiency (PCE) performances have been obtained with particular structures, front surface texture or rear surface field layer. In this paper, we provide a simple method without complex structures, and demonstrate the superiority and the mechanism of using stannic oxide (SnO2 ) as an insertion layer. The SnO2 insertion layer takes the place of the Schottky barrier, which reduces barrier height of rear Si to enhance charge transfer. And the effect of the insertion layer reduces contact resistance and enhances contact quality of rear Si side. Meanwhile, it has been indicated that the Si-O-Sn bonds were formed by SnO2 and Si dangling bond (Si-), which have a passivation effect on the Si surface to effectively suppress the recombination losses. Furthermore, simulations using density functional theory (DFT) confirm that the electrostatic potential can improve electronic transmission from Si to Sn between Si-O-Sn bonds. Finally, for the hybrid planar-Si/PEDOT:PSS heterojunction solar cells without any special structures, the highest PCE of 14.1% was achieved, up 10.8% compared with that without SnO2 insertion layer. These findings provide an effective way of improving Si/metal contact via a simple, room temperature process for other photovoltaic devices.